ANALISIS KESULITAN BELAJAR MENURUT COONEY PADA MATERI BENTUK ALJABAR DITINJAU DARI KECEMASAN MATEMATIS PESERTA DIDIK - Teni Andriani; Supratman Supratman; Puji Lestari (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
This study aims to determine and describe learning difficulties according to Cooney on algebraic from material in terms of students’ mathematical anxiety. This research is qualitative descriptive research. The research subjects were selected as many as 5 (five) who met the criteria in accordance with the research objective of 57 students. Based on the results of the study, it is concluded that students experience different mathematical anxiety when working on math problem in each somatic aspect, cognitive aspect, attitude aspect and mathematical knowledge aspect. Learners with different levels of mathematical anxiety have different learning difficulties. Learners with very high anxiety levels and high anxiety levels experience difficulties in each indicator of difficulty. Learners with moderate anxiety levels do not experience difficulties in the use of concepts, but difficulties in the use of principles and solving verbal problems. Learners with low anxiety levels did not experience difficulties in the use of principles and solving verbal problems but sometimes had difficulty in using principles. Learners with very low anxiety levels did not experience difficulties with each indicator. The Factors that cause mathematical anxiety and mathematics learning difficulties arise because students feel nervous about explaining the results of mathematical work in front of the class because they are not sure that the answers given are correct. Keywords: Mathematical Anxiety, Learning Difficulties, Algebra